Length-weight relationship, condition factors and reproductive biology of the spineless cuttlefish Sepiella inermis (Ferussac & d’Orbigny, 1848) in the southeastern regions of the Bay of Bengal, Bangladesh - Roksana Jahan; Md. Nasim Mahmud (Heliyon)
Sepiella inermis, spineless and small-size cuttlefish, is one of the important species of cephalopods and widely distributed in the Indo-west Pacific region. This study, for the first time in the southeastern region of the Bay of Bengal, Bangladesh, was conducted to investigate the length-weight relationship, condition factors and spawning season of S. inermis. Samples (∼149) were collected monthly from the Bangladesh Fisheries Development Corporation (BFDC) landing center, Cox's Bazar from July 25, 2022 to May 15, 2023. Females were dominant throughout the year. Female exhibited higher dorsal mantle length (DML, 6.56 cm) and body weight (BW, 41.55 g) than males. b value of the length-weight (DML vs BW) relationship of female and male was 1.912 (r2 = 0.5072, p < 0.001) and 2.119 (r2 = 0.9557, p < 0.001), respectively, which indicated a negative allometric growth pattern. The Fulton's, relative condition factors and relative weight fluctuated based on sexes and seasons. Five gonadal (immature, maturing, mature, spawning, and spent) and four testis maturation stages were observed. The highest percentage of mature females (100 %) and males (75 %) were observed between 10-10.99 and 9–9.99 cm DML, respectively. 50 % of the females and males matured at 7.2 cm and 5.2 cm DML, respectively. On average, females have a greater gonadosomatic index (6.87 %) than males (1.98 %). A major peak in GSI of females was observed in September 2022, and second peak was in January 2023. The major spawning season in males was observed during January and May 2023. GSI had a negative correlation with condition factors in females and males. Since this is the baseline study on the reproduction aspects of S. inermis, further study could consider the effects of oceanographic and climatic parameters on the abundance and reproduction of cuttlefish in the Bay of Bengal.